2017
DOI: 10.1186/s12891-016-1370-7
|View full text |Cite
|
Sign up to set email alerts
|

A 12-week randomized, double-blind, placebo-controlled multicenter study of choline-stabilized orthosilicic acid in patients with symptomatic knee osteoarthritis

Abstract: BackgroundThe aim of this study was to assess the efficacy of choline-stabilized orthosilicic acid (ch-OSA) in patients with symptomatic knee osteoarthritis (OA).MethodsIn a multicenter, double-blind, placebo-controlled study, 211 patients with knee OA (Kellgren and Lawrence grade II or III) and moderate to moderately severe pain were randomly allocated to ch-OSA or placebo for 12 weeks. The primary outcome was the change in the WOMAC pain subscale from baseline to week 12. Secondary outcomes were changes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…According to the authors, such results might be connected with the fact that the female subjects were mostly postmenopausal, and the serum baseline estradiol in this group was much lower than in males. This made the 12-week treatment too short and consequently ineffective [31]. Such conclusions are consistent with the results reported by Macdonald et al who stated that silicon influence on bone condition was affected by oestrogen status.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to the authors, such results might be connected with the fact that the female subjects were mostly postmenopausal, and the serum baseline estradiol in this group was much lower than in males. This made the 12-week treatment too short and consequently ineffective [31]. Such conclusions are consistent with the results reported by Macdonald et al who stated that silicon influence on bone condition was affected by oestrogen status.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the associations between silicon metabolism and female hormones have been investigated and relationships of Si bone metabolism with oestrogen status revealed [25,29]; however, other authors did not find any correlations of its absorption and excretion with oestradiol [30]. Additionally, the differences between the male and female studied groups regarding the beneficial influence of silicon preparation treatment in knee OA patients have been reported [31]. Some interactions between silicon and other elements have also been observed [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Some papers have shown a significant correlation between radiographic progression of OA and CTX-II concentration [33]. It has been reported to be the best performing biochemical markers for OA [34]. This study revealed that the change of serum IGF-1, OPN, and CTX-II was consistent with those in SF.…”
Section: Discussionsupporting
confidence: 74%
“…Persons with OA is limited their physical activities due to this disease and their quality of life is also declined [21]. Disease modifying agents for OA is not available, treatment strategies are directed to relieve symptoms that are correlated to this disease [4]. In this study, there were three patients who reported the mild adverse effect of KT (mild itchy) but received complete intervention without requiring medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for the course of condition of OA has not available yet. Therefore, treatment approaches are focused on relieving symptoms of disease [4]. Current OA knee treatment strategies include pharmacologic, nonpharmacologic and surgical managements [2].…”
Section: Introductionmentioning
confidence: 99%